Sodium‐dependent transport of ascorbic acid in U937 cell mitochondria. Issue 2 (3rd January 2013) - Azzolini, Catia; Fiorani, Mara; Cerioni, Liana; Guidarelli, Andrea; Cantoni, Orazio
Abstract U937 cells exposed to physiological concentrations of ascorbic acid (AA) accumulate the reduced form of the vitamin in the cytosol and even further in their mitochondria. In both circumstances, uptake was dependent on Na+‐AA‐cotransport, with hardly any contribution of hexose transporters, which might be recruited to transport the oxidized form of the vitamin. There was an identical linear relationship between the mitochondrial accumulation of the vitamin and the extramitochondrial AA concentration, regardless of whether detected in experiments using intact cells or isolated mitochondria. Western blot experiments revealed expression of both SVCT1 and 2 in plasma membranes, whereas SVCT2 was the only form of the transporter expressed at appreciable amounts in mitochondria. These results therefore provide the novel demonstration of SVCT2‐dependent mitochondrial transport of AA and hence challenge the present view that mitochondria only take up the oxidized form of the vitamin. © 2013 IUBMB Life, 65(2)149–153, 2013